Особливості інтерпретації мотивів та образів Т. Шевченка у творчості поетів «Української хати» - Шевель, Наталія; Shevel, Nataliay (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті досліджено особливості впливу особистості Т. Шевченка, мотивів та образів його творчості на доробок поетів «Української хати»; визначено традиції й новаторство художньої інтерпретації актуальних для модерністів образів, зокрема народного співця, кобзи, туману, ночі; з’ясовано зумовленість специфіки образності. ». In the article the features of the influence of Shevchenkoʼs personality, motives and images of his poetic heritage on the works of eminent poets of the «Ukrainian house», well Maintained, A. Nepritsky-Granovsky, N. Shapoval, Y. Budyak, A. Kovalenko, due to the tendency of poets-modernists to organic synthesis of nationalist ideology and aesthetics of modernism. Defined the tradition and innovation of artistic interpretations relevant to the modern Shevchenko images, in particular folk singer, kobza, fog, night, use, form of sleep. Discovered a conscious effort orienteering poets «Ukrainian house» on concrete poetry by T. Shevchenko in terms suggestive effect on the reader means receptive of poetics. Analyzed the problem of the creation of the cult of Shevchenko, which disturbed the members of the Association, and marked the credibility of his personality.
The Interpretation of Motives and Images of T. Shevchenko in the Works of Poets of the «Ukrainian House»
Keywords: модернізм; символізм; «Українська хата»; традиційні образи; новаторство; modernism; symbolism; «Ukrainian house»; traditional; innovation